Structure and transcription of the mouse erythropoietin receptor gene. - Youssoufian, H (1990)
The complete gene encoding the mouse erythropoietin receptor was isolated by using a cDNA probe derived from a mouse erythroleukemia (MEL) cell library. The gene spans approximately 5 kilobases and is present in a single copy per haploid genome. It contains eight exons, and the nucleotide sequence of the coding region from the genomic DNA is identical to the sequence of one of the MEL cDNA clones except for a single amino acid substitution (Leu----Val) at codon 163. There is a cluster of three major transcriptional start sites approximately 150 nucleotides upstream of the initiator ATG codon which is conserved in erythropoietin-dependent and -independent erythroleukemic cells, in MEL cells at different stages of differentiation, and in normal bone marrow cells. The promoter region contains a potential binding site for Sp1, erythroid-specific transcription factor GF-1, and several CACCC boxes, but not typical TATA or CAAT sequences. A fusion gene containing 452 nucleotides of 5' noncoding sequence linked to a promoterless human growth hormone gene directed the transcription of the latter in MEL cells but not in mouse fibroblasts, T cells, B cells, or macrophagelike cells, suggesting that this promoter functions in an erythroid-specific manner.